2015
DOI: 10.14374/hfs.2015.23.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Effects of Oldenlandia diffusa extract on WiDr human colorectal adenocarcinoma cells

Abstract: Objectives : The purpose of this study was to investigate the anti-cancer effects of Oldenlandia diffusa extract on WiDr human colorectal adenocarcinoma cells.Methods : We examined cell death by (3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide) MTT assay and the caspase 3 and 9 activity assay with Oldenlandia diffusa extract. To examine the inhibitory effects of Oldenlandia diffusa extract, we performed a cell cycle (sub-G1) analysis and mitochondrial membrane potential for the WiDr cells after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[6] There are 171 known components of HDW , which have been reported to exert antitumor, immunomodulatory, anti-inflammatory, neuroprotective, and anti-fibrotic effects. [7] In Korea, there have been studies on the anticancer [8] and antiallergic effects [9] of HDW, while other studies conducted in China have shown that HDW can have significant effects in the prevention and treatment of acne, [10,11] and it is therefore also used clinically for acne diseases. Currently, clinical studies are being conducted in China to confirm the effect of HDW on acne.…”
Section: Introductionmentioning
confidence: 99%
“…[6] There are 171 known components of HDW , which have been reported to exert antitumor, immunomodulatory, anti-inflammatory, neuroprotective, and anti-fibrotic effects. [7] In Korea, there have been studies on the anticancer [8] and antiallergic effects [9] of HDW, while other studies conducted in China have shown that HDW can have significant effects in the prevention and treatment of acne, [10,11] and it is therefore also used clinically for acne diseases. Currently, clinical studies are being conducted in China to confirm the effect of HDW on acne.…”
Section: Introductionmentioning
confidence: 99%